Barreras y dificultades para la implementación del sistema HACCP en empresas de alimentos de Lima, Perú - Sotomayor Quispe, Karen (2023)
In Peru, only 1 % of food processing companies located in Metropolitan Lima have obtained a technical validation for their HACCP plan. The low adherence to safety systems raises the goal of identifying the main barriers and difficulties for the implementation of the HACCP system. Data was collected by sending a questionnaire to 32 companies. In order to define the underlying structure of the barriers and difficulties identified we performed an exploratory factor analysis (EFA) and confirmatory factor analysis (CFA) based on a selection of nineteen (19) items, identifying four new factors that account for 66,7 % of the overall variability. After assessing their relevance, it was found that barriers and difficulties at the organizational/managerial level (F1) and in adaptation (F4), such as infrastructure and employee’s perception, were more relevant than attributes involving execution (F2), which comprises singular processes such as time, staff turnover, technology and others.